Cutaneous Allodynia in Migraine: A Narrative Review - Mínguez-Olaondo, Ane; Quintas, Sonia; Morollón Sánchez-Mateos, Noemí; López-Bravo, Alba; Vila-Pueyo, Marta; Grozeva, Vesselina; Belvís, Robert; Santos-Lasaosa, Sonia; Irimia, Pablo (Frontiers in Neurology, 2022)
OBJECTIVE: In the present work, we conduct a narrative review of the most relevant literature on cutaneous allodynia (CA) in migraine. BACKGROUND: CA is regarded as the perception of pain in response to non-noxious skin stimulation. The number of research studies relating to CA and migraine has increased strikingly over the last few decades. Therefore, the clinician treating migraine patients must recognize this common symptom and have up-to-date knowledge of its importance from the pathophysiological, diagnostic, prognostic and therapeutic point of view. METHODS: We performed a comprehensive narrative review to analyze existing literature regarding CA in migraine, with a special focus on epidemiology, pathophysiology, evaluation tools, risk for chronification, diagnosis and management. PubMed and the Cochrane databases were used for the literature search. RESULTS: The prevalence of CA in patients with migraine is approximately 60%. The mechanisms underlying CA in migraine are not completely clarified but include a sensitization phenomenon at different levels of the trigemino-talamo-cortical nociceptive pathway and dysfunction of brainstem and cortical areas that modulate thalamocortical inputs. The gold standard for the assessment of CA is quantitative sensory testing (QST), but the validated Allodynia 12-item questionnaire is preferred in clinical setting. The presence of CA is associated with an increased risk of migraine chronification and has therapeutic implications. CONCLUSIONS: CA is a marker of central sensitization in patients with migraine that has been associated with an increased risk of chronification and may influence therapeutic decisions.